2021
DOI: 10.1111/omi.12351
|View full text |Cite
|
Sign up to set email alerts
|

NEAT1 and MALAT1 are highly expressed in saliva and nasopharyngeal swab samples of COVID‐19 patients

Abstract: COVID‐19, caused by the SARS‐CoV‐2 virus, has become a significant global public health problem, with a wide variety of clinical manifestations and disease progression outcomes. LncRNAs are key regulators of the immune response and have been associated with COVID‐19 risk infection. Previous studies focused mainly on in‐silico analysis of lncRNA expression in the lungs or peripheral blood cells. We evaluated the expression of lncRNAs NEAT1, MALAT1, and MIR3142 in saliva and nasopharyngeal swab from SARS‐CoV‐2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 17 publications
4
20
0
Order By: Relevance
“…Among 66 deregulated lncRNA observed in the present study, expression of 17 lncRNA in the same direction has been reported by others; expression of 39 lncRNA has not yet been published and expression 10 lncRNA has been shown to alter in opposite direction (Table S9). Very recently it has been shown that that NEAT1 and MALAT1 are highly expressed in saliva and nasopharyngeal swab samples of COVID-19 patients [118] confirming the result in the present study. Increased in our earlier study [34] HCG11, HIF1A-AS2, LINC00115, LINC00174, LINC00265, LINC00312, LINC00473, LINC00605, LINC00662, LINC00842, MALAT1, MEG3, MEG9, MIAT, NEAT1, RMRP, hTR/TERC, ZNF674-AS1 (20) Decreased in the present study ARIH2OS, C1orf220, DANCR, DGCR5, DHRS4-AS1, DLEU1, DLGAP1-AS1, FAM201A, FLJ20021, FOXN3-AS1, GAS6-AS1, H19, KANSL1-AS1, LINC00526, LINC00707, LINC00880, LINC00893, MIR1915HG, NBR2, NCBP2AS2, PXN-AS1, RASSF8-AS1, SLC22A18AS, SLC25A21-AS1, SNHG32, SNHG5, SNHG9, ST7-AS1, TMEM161B-AS1, TMEM99, TMPO-AS1, TP53TG1, and WAC-AS1 (33) Decreased in our earlier study [34] LINC00488, LINC00857, PART1, and TP53TG1 (4)…”
Section: For Comparison Of Different Set Of Genes/proteinssupporting
confidence: 93%
“…Among 66 deregulated lncRNA observed in the present study, expression of 17 lncRNA in the same direction has been reported by others; expression of 39 lncRNA has not yet been published and expression 10 lncRNA has been shown to alter in opposite direction (Table S9). Very recently it has been shown that that NEAT1 and MALAT1 are highly expressed in saliva and nasopharyngeal swab samples of COVID-19 patients [118] confirming the result in the present study. Increased in our earlier study [34] HCG11, HIF1A-AS2, LINC00115, LINC00174, LINC00265, LINC00312, LINC00473, LINC00605, LINC00662, LINC00842, MALAT1, MEG3, MEG9, MIAT, NEAT1, RMRP, hTR/TERC, ZNF674-AS1 (20) Decreased in the present study ARIH2OS, C1orf220, DANCR, DGCR5, DHRS4-AS1, DLEU1, DLGAP1-AS1, FAM201A, FLJ20021, FOXN3-AS1, GAS6-AS1, H19, KANSL1-AS1, LINC00526, LINC00707, LINC00880, LINC00893, MIR1915HG, NBR2, NCBP2AS2, PXN-AS1, RASSF8-AS1, SLC22A18AS, SLC25A21-AS1, SNHG32, SNHG5, SNHG9, ST7-AS1, TMEM161B-AS1, TMEM99, TMPO-AS1, TP53TG1, and WAC-AS1 (33) Decreased in our earlier study [34] LINC00488, LINC00857, PART1, and TP53TG1 (4)…”
Section: For Comparison Of Different Set Of Genes/proteinssupporting
confidence: 93%
“…The higher expression level of lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1/NEAT2) has been considered to have a critical role in inflammation and cytokine production. Similar results were also observed in saliva and nasopharyngeal swabs of COVID-19 patients [ 74 ], however, details of the mechanisms of MALAT1 upregulation and the cytokine production mediated by MALAT1 in COVID-19 have not been well illustrated. Herein, we identified TF XBP1 as one of the upstream nodes of lncRNA MALAT1.…”
Section: Resultssupporting
confidence: 75%
“…Furthermore, the datasets we analyzed were generated from patient samples collected between January and April 2020, before the first SARS-CoV-2 variants were designated by the World Health Organization. While the overall trends in our data are reflected in recent work on lncRNAs in COVID-19, there remains a lack of variant specific studies [ 85 ]. Additional work on the expression of lncRNAs in variant specific samples may uncover further insights.…”
Section: Discussionmentioning
confidence: 99%